Mountain biking injuries: an update. - Kronisch, R. L.; Pfeiffer, R. P. (Sports Medicine, 2002)
This article reviews the available literature regarding injuries in off-road bicyclists. Recent progress in injury research has allowed the description of several patterns of injury in this sport. Mountain biking remains popular, particularly among young males, although sales and participation figures have decreased in the last several years. Competition in downhill racing has increased, while cross-country racing has decreased somewhat in popularity. Recreational riders comprise the largest segment of participants, but little is known about the demographics and injury epidemiology of noncompetitive mountain cyclists. Most mountain bikers participating in surveys reported a history of previous injuries, but prospective studies conducted at mountain bike races have found injury rates of <1%. The most common mechanism of injury involves a forward fall over the handlebars, usually while riding downhill, which can result in direct trauma to the head, torso and upper extremities. A variety of factors can be associated with this type of fall, including trail surface irregularities, mechanical failures and loss of control. In mountain bike racing the risk of injury may be higher for women than men. Minor injuries such as abrasions and contusions occur frequently, but are usually of little consequence. Fractures usually involve the torso or upper extremities, and shoulder injuries are common. Head and face injuries are not always prevented by current helmet designs. Fatal injuries are rare but have been reported. Improvements in safety equipment, rider training and racecourse design are suggested injury prevention measures. The authors encourage continued research in this sport.